MAKNA DAN NILAI MORAL RITUAL ADAT HELA KETA DALAM PERKAWINAN SUKU AMANUBAN DAN MOLLO DI KABUPATEN TTS - Lili Missa; Hiwa Wonda (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to explore the meaning and moral values contained in the Hela Keta traditional ritual practiced by the Amanuban and Mollo communities in South Central Timor Regency. The ritual plays an important role in traditional marriage as it serves to reconcile and unite two groups that were once bound by an ancestral oath prohibiting intermarriage due to past conflicts. The research applied a descriptive qualitative approach consisting of two stages: library research and fieldwork. Data were collected through interviews with traditional leaders, community elders, and local authorities in Kesetnana Village, South Mollo District. The results show that Hela Keta holds deep symbolic meanings, such as the river symbolizing purification and peace, the sacrificial animal representing sincerity and reconciliation, and the communal meal reflecting unity and equality. The moral values found in this ritual include honesty, responsibility, brotherhood, peace, and respect for ancestors. These values represent the local wisdom of the Timorese people in maintaining social harmony and can serve as a source for character education in social studies learning.